INTERSTITIAL LUNG DISEASES AND SECONDARY PULMONARY HYPERTENSION - Belić, Slobodan; Marić, Nikola; Đurđević, Nataša; Golubović, Aleksa; Milivojević, Ivan; Geratović, Miloš; Nikolić, Nikola; Čokrlić, Irina; Stjepanović, Mihailo (Srpski medicinski časopis Lekarske komore, 2023)
Interstitial lung disease alone can have a poor prognosis, and when associated with pulmonary hypertension there is a significant reduction in survival rates. Since the incidence of pulmonary hypertension in patients with interstitial lung diseases is very high and the symptoms are similar and often unrecognized, our aim is to point out the significance of both coexisting diseases and to prompt clinicians to suspect pulmonary hypertension. Through a brief review of the pathohistological changes, diagnostic methods, and the clinical presentation of these diseases, the similarities and differences that can help in the management of these patients, are shown. The latest treatment guidelines, with a special focus on the impact of antifibrotic treatment (nintedanib and pirfenidone) on pulmonary hypertension, are presented.